SIMULASI POLA DIFRAKSI FRAUNHOFER UNTUK CELAH LINGKARAN DENGAN MODIFIKASI FUNGSI BESSEL - Cecilia Yanuarief (UIN Sunan Kalijaga Yogyakarta, 2018)
This research aims to simplify the equation of Fraunhofer Difraction Intensity for the circular slit analyticaly so that it can be easily applied in the calculation of computing. Fraunhofer diffraction event for the circular slitis expressed as the ratio between Bessel functions 1 and variables with interval 0 to infinity so may result divided by zero in the calculation of computing. Solution analytical calculations done by outlining the Bessel function 1 becomes the Bessel function 0 and Bessel functions 2. The results of analytical calculations and computations, Fraunhofer diffraction pattern is obtained in the form of the intensity curve which is then displayed in 3D to get the diffraction pattern.From the results of this research concluded that the larger radius gap, resulting the diffraction pattern is getting narrower. And the greater the wavelength of the light source, resulting diffraction pattern is widening.